2016
DOI: 10.1111/1471-0528.14145
|View full text |Cite
|
Sign up to set email alerts
|

Do pelvic floor muscle exercises reduce postpartum anal incontinence? A randomised controlled trial

Abstract: Objective To evaluate the effect of pelvic floor muscle exercises (PFME) for postpartum anal incontinence (AI).Design A parallel two-armed randomised controlled trial stratified on obstetrical anal sphincter injury with primary sphincter repair and hospital affinity.Setting Ano-rectal specialist out-patient clinics at two hospitals in Norway.Population One hundred and nine postpartum women with AI at baseline. MethodsThe intervention group received 6 months of individual physiotherapy-led PFME and the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 32 publications
4
39
2
1
Order By: Relevance
“…1 We agree that GWG and obesity in pregnancy are important, partly overlapping factors in adverse pregnancy outcomes, and that a significant amount of research has focused on methods to reduce GWG. We note that in meta-analysis, dietary interventions appear to be most successful at reducing GWG, compared with exercise or other interventions, but studies have shown mixed results in reducing the incidence of other important adverse maternal and neonatal outcomes.…”
Section: Sirmentioning
confidence: 86%
See 2 more Smart Citations
“…1 We agree that GWG and obesity in pregnancy are important, partly overlapping factors in adverse pregnancy outcomes, and that a significant amount of research has focused on methods to reduce GWG. We note that in meta-analysis, dietary interventions appear to be most successful at reducing GWG, compared with exercise or other interventions, but studies have shown mixed results in reducing the incidence of other important adverse maternal and neonatal outcomes.…”
Section: Sirmentioning
confidence: 86%
“…2 Our study and others' results have led us to revise our initial hypothesis: we now feel that serial self-weighing alone is unlikely to alter GWG or health outcomes for overweight and obese women and their children in any predictable way. 1,3 Nevertheless, it is extremely reassuring to know that women do not suffer anxiety or diminished quality of life when they participate in research aimed at controlling GWG. 1,4 We anticipate that serial self-weighing will remain in research and clinical practice.…”
Section: Sirmentioning
confidence: 99%
See 1 more Smart Citation
“…PFM training is the first line of conservative management for women with different symptoms of pelvic floor dysfunction Beji et al 2003;Dean et al 2008;Hagen and Stark 2011;Braekken et al 2015;Hagen et al 2017;Johannessen et al 2017), promoting pelvic organ support and control of the continence mechanism, along with better awareness of the pelvic floor structures, self-confidence and libido. Pompoir practice is not particularly focused on treating or preventing pelvic floor symptoms, but on improving coordination capacities of the PFM, being reported by practitioners to promote benefits on sexual function and self-awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also indicated that PFM training have a positive impact on sexual functions by increasing self-confidence, desire, lubrication, orgasm, and satisfaction Beji et al 2003;Dean et al 2008;, although it has been suggested that more high quality clinical trials would be necessary to confirm these findings (Bø 2012;Ferreira et al 2015). Most recently, benefits of PFM training were reported for anal incontinence (Johannessen et al 2017), and for the prevention and reduction of symptoms and severity of pelvic organ prolapse (Hagen and Stark 2011;Hagen et al 2017), pointing out that intervention for treatment and prevention of these dysfunctions should be encouraged on the basis of it being safe and done easily by most women.…”
Section: Introductionmentioning
confidence: 99%